A Late Oligocene Drowned Pinnacle Reef in Deepwater Makassar Straits - J.T. (Han) van Gorsel; C.E. Helsing (Ikatan Ahli Geologi Indonesia, 2014)
A steep seamount with 320-350m of relief was recently discovered in about 2050m deep water of the South Makassar Straits. It was informally named Snorkel by ExxonMobil interpreters, but remains unnamed. Drop core samples collected from different levels of the buildup by ExxonMobil in 2008 show the Snorkel feature to be an Oligocene pinnacle reef, which drowned in latest Oligocene time.The carbonate buildup is covered in a thin coating of ferro-manganese cement, representing over 20 Million years of exposure and non-deposition in a deep water environment.The Snorkel feature is one of the many carbonate buildups that formed on Sundaland and around its margins after a Middle-Late Eocene regional rifting/subsidence event (e.g. 'Berai Limestone' of East Kalimantan), but until now is the only known example of an Oligocene reefal buildup that was never buried under younger sediments.